Assessing The Potential Area For Rice-Fish Systems In Mali - Teoh, Shwu. J; Dossou-Yovo, E. R (2024)
Integrated rice-fish farming offers a climate-smart approach to enhance food security, improve ecosystem services, and boost resilience to climate variability. This study aimed to map rice-fish suitability in Mali using GIS-based multi-criteria evaluation (MCE) techniques and integrating biophysical and socio-economic factors. Four regions—Segou, Koulikoro, Sikasso, and Bamako—were assessed, with inputs from stakeholder consultations to refine criteria. The results were validated against data collected on rice fish fields and fishponds. Substantial areas were classified as "Most Suitable," notably in Koulikoro and Segou. Despite limitations, such as the absence of climate dimensions and limited validation points, the findings provide a robust foundation for guiding sustainable development and investment in rice-fish systems. Incorporating climate factors and improving validation processes will further enhance this approach reliability and scalability for planning integrated rice-fish scaling in Mali.